Analysis of Two Aristocratic Handwritten Cookery Books and One Collection of Recipes from 19th Century - Miklovičová, Lucie (Theatrum historiae, 2013)
The article deals with the boarding habits of aristocracy in 19th century. The first part of research work focuses on sources, which we can use for studying boarding habits, not only at aristocratic courts. The primary aim is the analysis of cookbooks in more detail, namely cookbook of Filipina Schlik and Ludmila Berchtold and collection of recipes by Marie Thun, notably their structure and content. The attention is focused to the foodstuffs, the way they were handled and arrange. Banquet menus, breakfasts and behavior during dining are next point of the research.